Exploration of Oil Bunkering in Chimeka Garrick’s Tomorrow Died Yesterday - Omesu, Modupeoluwa; Onwuka, Edwin (Khwopa Journal, 2025)
This study examines the pervasive issue of oil bunkering in the Niger Delta region of Nigeria through a textual analysis of Chimeka Garricks’ Tomorrow Died Yesterday. The Niger Delta, is a region abundant in natural resources, has been plagued by illegal oil extraction, environmental degradation, and socio-political disruption. Garricks’ novel offers a nuanced literary portrayal of these crises, highlighting the interplay between economic desperation, militant insurgency, and governmental corruption. This study aims to examine the representation of oil bunkering in Chimeka Garricks’ Tomorrow Died Yesterday as a central socio-political and economic concern in the Niger Delta. And to also explore how the novel critiques systemic corruption, government complicity, and the failure of legitimate structures, which enable the persistence of illegal oil activities. The study is a qualitative methodology that use the text as a reflection of the Niger Delta realities and also criticticlly examines the root causes of oil bunkering and the aftermath as reflected in the text Tomorrow Died Yesterday engages with themes of environmental destruction and political corruption, it does not extensively examine the intricate operations of oil bunkering and its socio-economic networks. This study seeks to fill that gap by analyzing the novel’s portrayal of oil bunkering, foregrounding it as a critical issue rather than a peripheral theme. Through a transactional reader reponse theory, this research unpacks the thematic concerns surrounding oil bunkering, shedding light on its ramifications for both the environment and local communities. The study underscores how Garricks utilizes narrative techniques, character development, and setting to critique the exploitative dynamics in the oil-rich region. By exploring the intersections of literature, socio-political commentary, and environmental justice, this research contributes to broader discussions on resource control, state violence, and ecological sustainability in postcolonial African literature. Ultimately, this study highlights how fiction can serve as both a historical record and a call to action for socio-environmental justice in the Niger Delta.